Homoeopathy In Management of Alopecia Areata – A Narrative Review (Advancements in Homeopathic Research, 2023)
Background: Alopecia areata is a form of alopecia  that affects hair follicles. It presents with round  patch. Many treatments are available and this review  highlights the usage of homoeopathy in treatment of  alopecia areata. Objective: The review was done to explore the  strengths of homoeopathy in management of alopecia  areata through online available evidences. Methods: A search was made for homoeopathic  management of Alopecia areata in PubMed, AYUSH  Research Portal, Google Scholar, Google search  engines was done to collect all relevant articles,  reports, web pages published till October 2022.  The term included was Alopecia homoeopathic  treatment, Alopecia homoeopathy, Alopecia areata  homoeopathy. Further literature review was also  conducted & repertory was also searched. Result: 16 studies were found and all are case reports  except one. Conclusion: At present available evidences for  homoeopathic management of alopecia are very  weak. Further studies are needed for strong evidences.
Keywords: Alopecia; Homoeopathy; Review; Alopecia areata; Google search